Soil Pollution Assessment from Industrial Area of Erbil City - Khudhur, Shelan Mustafa; Khudhur, Nashmeel Saeed (Sulaimani Journal for Pure and Applied Sciences, 2015)
Present study assessed soil pollution by heavy metals and spent oil in three industrial areas of Erbil City. Soil pH ranged from 7.53±0.017 to 8.25±0.012 and EC was ranged between 103±0.882 and 465±9.955. Soils textures were loamy sand for south industry, sandy for oil selling area and north industry while loamy for control soil. The ranges of Pb, Zn and Ni were between 1.26±0.069 and 17.472±0.058; 1.439±0.006 and 3.078±0.003, and 0.399±0.061 and 0.982±0.048 ppm, respectively. The concentrations of Cd and Cr were below the detection limit and Cu levels varied from 10.307±0.334 to 0.063±0.003 ppm, whereas Cu was not detected in some sites. The highest oil residue was obtained in site 6. Oil and grease content for the groundwater samples in the studied sites were zero. Pearson’s correlation showed a significant positive correlation between Ni and moisture content and Ni and bulk density, beside to a moderate correlation between Pb and Zn. A high significant negative correlation was detected between bulk density and oil content. The lateral distribution of the heavy metals and oil residues showed higher average concentrations at the point of impact than 20 meters away. Relative Pollution Potential gave positive values for the metals and oil contents in all sites.
Keywords: Soil pollution; Heavy metals; Oil residues; Industrial area